Vagus Nerve Ultrasound in Diabetic Neuropathy: A Possible Detector of Autonomic Parasympathetic Neuropathy - F. Sartucci; M. Santin; T. Bocci; A. Filippi; N. Origlia; P. Marchetti (Research Developments in Medicine and Medical Science Vol. 3, 2023)
It is well known that a very common complication of diabetes mellitus (DM) is the somatic diabetic demyelinating distal sensory-motor polyneuropathy (D-DSP); autonomic neuropathy may be part of the disease and leads to high morbidity and mortality. Vagus Nerve (VN) is the longest autonomic nerve and often parasympathetic involvement precedes sympathetic symptoms. In this chapter, the authors illustrate and discuss the role of High Resolution Ultrasounds (HRUS) in detecting changes of the VN following their investigation in a group of DM patients with or without autonomic symptoms and neuropathy. The VN has been scanned in 20 healthy volunteers and 61 patients (32 m, 29 f) with DM in the axial plane at the lateral neck. The acquisition of ultrasound images was performed using a 19MHz probe with an Esaote MyLab Gamma device; cross-sectional area (CSA), perimeter, echogenicity and echo-structure were considered. Mean cross-sectional area of the vagus nerve resulted significantly smaller (3.13 mm2; SD = 1.54) in patients with diabetes compared with controls (5.8 mm2, DS = 1.2) and did not correlate with disease duration and parameters of cardiovagal functions. Data of this study, reported and analyzed in the present chapter, prove a degree of vagus nerve atrophy in DM patients. Moreover, HRUS finding may have relevance in the diagnosis and management of diabetic neuropathy, overall on parasympathetic involvement, even if further investigations need to confirm the relevance of these morphological findings.